The Ilocos Norte Communities against Rabies Exposure Elimination Project in the Philippines: Epidemiological and Economic Aspects - Valenzuela, Loida M.; Jayme, Sarah I.; Amparo, Anna Charinna B.; Taylor, Louise H.; Dela Cruz, Maria Pinky Z.; Licuan, Dianne A.; Gamal-Bitao, Rosebelle; Nel, Louis H. (Frontiers in Veterinary Science, 2017)
As canine rabies control in Africa and Asia transitions from research-led proof-of-concept studies to government-led programs for elimination, experience and evidence of their impact and costs must be shared for the benefit of future programs. The Ilocos Norte Communities against Rabies Exposure project was implemented in April 2012 by the provincial veterinary and health offices and supported by many other partners. It delivered a comprehensive dog vaccination program and increased awareness of the need for postexposure prophylaxis (PEP), aiming to eliminate human and animal rabies cases from Ilocos Norte by 2015. Prior to the intervention, confirmed rabies cases in dogs were between 19 and 50 per year (2008–2011). The primary outcome of the project was a reduction in rabies cases in both dogs and humans to 0 in 2014 and 2015, which has subsequently been maintained. Animal bite consultations increased significantly during the project. Economic data for the dog vaccination and PEP components of the project were collated for two sites: Laoag City (an urban setting) and Dingras Municipality (a rural setting) between 2012 and 2014. The average programmatic cost of vaccinating each dog was $4.54 in Laoag City and $8.65 in Dingras, and costs fell as the project reached more dogs. The average costs of providing PEP were $69.72 per patient and $49.02 per patient for the two sites, respectively, again falling as the project reached more people. External donor contributions contributed less than 20% of dog vaccination costs and less than 1% of PEP costs. The project demonstrated that rabies elimination can be achieved in a short period of time, with concerted effort across multiple sectors. A lack of clear dog population estimates hampered interpretation of some aspects of the programme. From 2016, the provincial government has assumed complete responsibility for the programme and must now continue the vaccination and surveillance efforts. Although safeguards are in place, reintroduction from surrounding areas remains a threat, and vigilance must be maintained.